Satisfaction and Technology Evaluation of a Telehealth Robotic Program to Optimize Healthy Independent Living for Older Adults. Issue 6 (15th October 2018) - Bakas, Tamilyn; Sampsel, Debi; Israel, Jahmeel; Chamnikar, Ameya; Ellard, Angela; Clark, John Greer; Ulrich, Megan Gresham; Vanderelst, Dieter
Abstract: Background and Purpose: With the growth in the aging population, and shortage of primary care providers, telehealth programs are needed to optimize healthy independent living for older adults. The purpose of this study was to evaluate a nurse‐led intervention program delivered through a telepresence robot to promote healthy lifestyles and address chronic illness management among older adults living independently in a retirement community. Telepresence robots provide two‐way video‐mediated communication with remote in‐home navigation. Design and Methods: Satisfaction and technology evaluation ratings of the Telehealth Community Health Assistance Team (T‐CHAT) program, as well as qualitative data from open‐ended questions, were obtained from 26 older adults and 7 nurse practitioner students. Findings: On a scale from 1 = strongly disagree to 5 = strongly agree, satisfaction ratings were positive for usefulness ( M = 3.90), ease of use ( M  = 4.16), and acceptability ( M = 4.06). Technology evaluation ratings were high for all sessions ( M = 4.35). Older adults and nurse practitioner students were highly complementary of the program. Areas for improvement were identified. Conclusions: The T‐CHAT program demonstrated high ratings for satisfaction (usefulness, ease of use, acceptability) and for evaluation of the telepresence robot technology. Further refinement of the T‐CHAT program is warranted, as is testing outcomes of this potentially viable mode of healthcare delivery. Clinical Relevance: Robotics is the wave of the future and provides an innovative mode of delivery to address health promotion and chronic illness management in older adults. Satisfaction and technology evaluation of robotic technology is paramount prior to implementation of such programs into practice.